Trophic ecology of largehead hairtail Trichiurus japonicus in the South Sea of Korea revealed by stable isotope and stomach content analyses - Shin, Donghoon; Park, Tae Hee; Lee, Chung-Il; Jeong, Jae Mook; Lee, Seung-Jong; Kang, Sukyung; Park, Hyun Je (Frontiers in Marine Science, 2022)
Largehead hairtail (Trichiurus japonicus) is one of the most commercially important fishes in the western North Pacific. To identify the dietary changes across ontogeny and seasons, we investigated its stomach contents and stable isotope signatures (δ13C and δ15N) in the South Sea of Korea. The index of relative importance revealed that the dietary composition of largehead hairtail consisted mainly of Pisces (1.6%–84.8%) and Euphausiacea (3.0%–93.0%). However, the proportions of dietary items differed by season and anal length (ALs), suggesting a trophic adaptability response to seasonal food availability and size-related trophic variation, respectively. Our isotopic results showed that the largehead hairtail is placed intermediately between pelagic and benthic fishes and was more 13C and 15N-depleted than other carnivorous fishes, suggesting a high consumption of pelagic species. Similarly, seasonal variations were observed in the δ13C and δ15N values of the largehead hairtails (PERMANOVA, p= 0.001). Interestingly, their δ13C values in spring decreased significantly with ALs (r2 = 0.594, p< 0.001), suggesting an ontogenetic change due to the increased proportion of Euphausiacea to the nutrition of largehead individuals during this specific season. Based on a combination of stomach contents and stable isotope signatures, overall results provide new insights into the feeding characteristics of the largehead hairtail, which improves our understanding of its trophic ecology depending on season and body size.